Fatigue in young adults with juvenile idiopathic arthritis 18 years after disease onset: data from the prospective Nordic JIA cohort - Ellen Dalen Arnstad; Mia Glerup; Veronika Rypdal; Suvi Peltoniemi; Anders Fasth; Susan Nielsen; Marek Zak; Kristiina Aalto; Lillemor Berntson; Ellen Nordal; Troels Herlin; Pål Richard Romundstad; et al. (BMC, 2021)
Abstract Background To study fatigue in young adults with juvenile idiopathic arthritis (JIA) 18 years after disease onset, and to compare with controls. Methods Consecutive children with onset of JIA between 1997 and 2000, from geographically defined areas of Norway, Sweden, Denmark and Finland were followed for 18 years in a close to population-based prospective cohort study. Clinical features, demographic and patient-reported data were collected. Inclusion criteria in the present study were a baseline visit 6 months after disease onset, followed by an 18-year follow-up with available self-reported fatigue score (Fatigue Severity Scale (FSS), 1-7). Severe fatigue was defined as FSS ≥4. For comparison, Norwegian age and sex matched controls were used. Results Among 377 young adults with JIA, 26% reported severe fatigue, compared to 12% among controls. We found higher burden of fatigue among participants with sleep problems, pain, poor health, reduced participation in school/work, physical disability, active disease, or use of disease-modifying anti-rheumatic drugs (DMARDs)/biologics/systemic steroids. In contrast, participants without these challenges, had fatigue scores similar to controls. Active disease assessed at all three time points (baseline, 8-year and 18-year follow-up) was associated with higher mean fatigue score and higher percentage of severe fatigue compared to disease courses characterized by periods of inactive disease. Predictors of fatigue at the 18-year follow-up were female sex and diagnostic delay of ≥6 months at baseline, and also pain, self-reported poor health, active disease, and previous/ongoing use of DMARDs/biologics at 8 years. Conclusions Fatigue is a prominent symptom in young adults with JIA, with higher fatigue burden among participants with poor sleep, pain, self-reported health problems, active disease, or use of DMARDs/biologics. Participants without these challenges have results similar to controls. Patient- and physician-reported variables at baseline and during disease course predicted fatigue at 18-year follow-up.